Flyttningar, socialt stöd och psykisk ohälsa (Sociologisk Forskning, 1993)
Internal migration, social support and mental illnessThis paper analyses whether internal migration has any negative effects on the mental health of mobile individuals. The study is based on 2042 persons who were interviewed in both the 1974 and 1981 Swedish level of living survey. Mental health is measured by several questions to the respondents about his/her psychological well-being and analyzed by means of logistic regression. For mobile men it is found that their mental health is poorer compared with non-mobile men; for women no such effect is found. Furthermore, the higher risk for mental ill health among mobile men can to a small degree be explained by health selection and social support. Before their migration the male migrants were in worse mental condition than the male non-migrants and the social support they received at their new place of residence was lower. The most striking result however, is that, among men, an interaction effect is found between geographical mobility and social support. Mobile men with low social support experience much more mental strain than both mobile men with high social support and non-mobile m en (with or without social support).